Association of Duration of Hypotension With Survival After Pediatric Cardiac Arrest. Issue 2 (February 2020) - Laverriere, Elizabeth K.; Polansky, Marcia; French, Benjamin; Nadkarni, Vinay M.; Berg, Robert A.; Topjian, Alexis A.
Abstract : Objectives: To evaluate the association of a single episode of hypotension and burden of hypotension with survival to hospital discharge following resuscitation from pediatric cardiac arrest. Design: Retrospective cohort study. Setting: Single-center PICU. Patients: Patients between 1 day and 18 years old who had a cardiac arrest, received chest compressions for more than 2 minutes, had return of spontaneous circulation for more than 20 minutes, and survived to receive postresuscitation care in the ICU. Interventions: None. Measurement and Main Results: One-hundred sixteen patients were evaluable. Hypotension, defined as systolic blood pressure less than the fifth percentile for age and sex, occurred in 37 patients (32%) within the first 6 hours and 64 (55%) within 72 hours of postresuscitation ICU care. There was no significant difference in survival to discharge for patients who had a single episode of hypotension within 6 hours (51% vs 69%; p = 0.06) or within 72 hours (56% vs 73%; p = 0.06). Burden of hypotension was defined as the percentage of hypotension measurements that were below the fifth percentile. After controlling for patient and cardiac arrest event characteristics, a higher burden of hypotension within the first 72 hours of ICU postresuscitation care was associated with decreased discharge survival (adjusted odds ratio = 0.67 per 10% increase in hypotension burden; 95% CI, 0.48–0.86; p = 0.006). Conclusions: After successful resuscitation from pediatric cardiac arrest, systolic hypotension was common (55%). A higher burden of postresuscitation hypotension within the first 72 hours of ICU postresuscitation care was associated with significantly decreased discharge survival, after accounting for potential confounders including number of doses of epinephrine, arrest location, and arrest etiology due to airway obstruction or trauma.